2009
DOI: 10.1007/s10803-009-0737-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Background Noise on Cortical Encoding of Speech in Autism Spectrum Disorders

Abstract: This study provides new evidence of deficient auditory cortical processing of speech in noise in autism spectrum disorders (ASD). Speech-evoked responses (~100-300 ms) in quiet and background noise were evaluated in typically-developing (TD) children and children with ASD. ASD responses showed delayed timing (both conditions) and reduced amplitudes (quiet) compared to TD responses. As expected, TD responses in noise were delayed and reduced compared to quiet responses. However, minimal quiet-to-noise response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 74 publications
(142 reference statements)
4
79
0
6
Order By: Relevance
“…Interestingly, individual differences in temporal resolution were positively related to speech-in-noise perception in the ASD sample, which suggests that impaired temporal perception at the ms scale may impact upon speech and language learning, possibly through less optimal consonant discrimination (Bhatara et al 2013). This fits with findings of electrophysiological studies showing reduced automatic discrimination of consonants in ASD (e.g., Jansson-Verkasalo et al 2003;Kuhl et al 2005;Russo et al 2009). …”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, individual differences in temporal resolution were positively related to speech-in-noise perception in the ASD sample, which suggests that impaired temporal perception at the ms scale may impact upon speech and language learning, possibly through less optimal consonant discrimination (Bhatara et al 2013). This fits with findings of electrophysiological studies showing reduced automatic discrimination of consonants in ASD (e.g., Jansson-Verkasalo et al 2003;Kuhl et al 2005;Russo et al 2009). …”
Section: Discussionsupporting
confidence: 90%
“…No differences in MMN or N1 between participants with autism and controls were found, suggesting largely intact initial auditory cortical processing and discrimination of syllables. Kuhl et al (2005) found impaired syllable discrimination, in line with Jansson-Verkasalo et al (2003) and Russo et al (2009). However, Kuhl et al were able to associate their findings with a non-speech sound preference.…”
Section: Acoustic and Phonetic Features Of Speech Soundssupporting
confidence: 74%
“…These studies mainly found evidence of impaired syllable discrimination (Jansson-Verkasalo et al, 2003;Kuhl et al, 2005;Russo et al, 2009), which seemed to be associated with a non-speech sound preference (Kuhl et al, 2005). Intact syllable discrimination in high functioning children with autism was found by Kemner et al (1995).…”
Section: Acoustic and Phonetic Processing Of Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…FFRs and EFRs are evoked in response to longer, often more spectro-temporally complex stimuli (Krishnan 1999(Krishnan , 2002Krishnan et al 2004;Swaminathan et al 2008), and are strongly influenced by rostral brainstem and midbrain generators (Kiren et al 1994;Kuwada et al 2002;Akhoun et al 2010;Chandrasekaran and Kraus 2010;Parthasarathy and Bartlett 2012). They have been used to show differences in processing of complex stimuli under various pathological conditions, such as age-related hearing loss, dyslexia, and autism (McAnally and Stein 1997;Chandrasekaran et al 2009;Russo et al 2009;Anderson et al 2012;Clinard and Tremblay 2013).…”
Section: Introductionmentioning
confidence: 99%